2021
DOI: 10.3390/su13042177
|View full text |Cite
|
Sign up to set email alerts
|

Development of Performance Evaluation Indicators for Table Grape Packaging Units

Abstract: In order to improve the process management of table grape packaging, its performance should be evaluated. However, the literature on performance evaluation indicators is scarce. To address this research gap, we propose a method for the development of performance evaluation indicators for table grape packaging units, which are characterized by labor-intensive and highly seasonal production processes in the agro-economic sector. The stages include the following: contextualizing table grape packaging units, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This gap in the scientific literature motivated this study: the development of a robust GI for the performance evaluation of TGPUs. The method proposed in this research was verified for TGPUs located in the vale do submédio São Francisco (VSSF; San Francisco lower middle valley), in northeast Brazil, using previously developed performance indicators [18]. The structure of the proposed method for developing a robust GI for TGPUs is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…This gap in the scientific literature motivated this study: the development of a robust GI for the performance evaluation of TGPUs. The method proposed in this research was verified for TGPUs located in the vale do submédio São Francisco (VSSF; San Francisco lower middle valley), in northeast Brazil, using previously developed performance indicators [18]. The structure of the proposed method for developing a robust GI for TGPUs is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 93%
“…The objective was to provide researchers with a set of recommendations on how to design, develop, and disseminate a GI. The authors suggested a checklist with ten items to be followed: AGR Min-Max (0-1) Participative (AHP) Linear [25] AGR Min-Max (0-1) Participative Linear [5] AGR Min-Max (0-1) Participative (AHP) Linear [26] ENV Min-Max (0-1) Equal Linear [27] ENV Min-Max (0-100) Participative Linear [28] ENV Min-Max (0-1) Participative (AHP); Statistic (PCA) Linear; Geometric [29] ENV Relative to the maximum; Z-scores Participative; Statistic (Factor analysis) Linear [30] ENV Relative to the maximum Equal Linear; Geometric [31] ENV Min-Max (0-1) Statistic (Entropy) Linear [32] ENV Min-Max (0-1) Statistic (Entropy) Linear [33] ENV Min-Max (0-100) Equal Linear This checklist was used as a guideline for this study, however, the first four of the ten suggestions will not be covered in this paper because they have already been addressed in our proposal for the development of performance indicators for production processes of TGPUs [18]. In addition, item 9 ("links to other variables") was not considered due to the absence of another GI that can be correlated to the one developed here.…”
Section: Global Indexes (Gis) Backgroundmentioning
confidence: 99%
See 2 more Smart Citations